Pemanfaatan Bahan Lokal dalam Pembuatan Mp-Asi Sebagai Upaya Pencegahan Stunting di Desa Cenrana Kabupaten Sidrap - St. Nurbaya; Nur Laela; Hamdiyah Hamdiyah; Rosmawaty Rosmawaty; Resmawati Resmawati (Yayasan Literasi Sains Indonesia, 2022)
Stunting is a condition of growth faltering in children under five due to chronic malnutrition, especially in the first 1,000 days of life (HPK). Stunting is caused by poor nutritional status of the mother during pregnancy, poor nutrition when the fetus is still in the womb, inadequate breastfeeding and also delayed complementary feeding and inadequate quality and quantity of complementary foods resulting in children experiencing low birth weight. Stunting can affect brain growth and development. One way that can be done in preventing stunting is by strengthening local wisdom. So far, the practice of providing complementary feeding (MPASI) to toddlers is often not considered, especially in terms of nutrient density. This is due to the lack of knowledge and skills of mothers under five in terms of how to make and serve nutrient-dense complementary foods. One of the factors that occur in the presence of malnutrition is the incidence of stunting. The location of this service activity is carried out in Cenrana Village, Panca Lautang District, Sidrap Regency which has a wealth of local food ingredients. The method of implementing this activity begins with a preliminary survey by exploring the problem of eating patterns to mothers of toddlers in Cenrana village, Sidrap Regency and to posyandu cadres, village midwives and puskesmas nutrition workers, followed by stunting counseling followed by demonstrations of making complementary feeding using local food. The results of the service to increase mother's knowledge in the management of local food ingredients into MP ASI to prevent stunting.